A study on building defects in newly completed high-rise residential buildings during defects liability period / Zarul Azkief Che Zulkifli - Che Zulkifli, Zarul Azkief (Faculty of Architecture, Planning and Surveying, 2009)
In recent times. buildings defects are constantly arising in Malaysia though it is a newly completed building. These might be happened due to the poor of workmanship and the use of less quality materials. Although the defects of new buildings are not that bad, but it is yet to demonstrate that the supervisory levels during the constructions practice are still insufficient. As the results, developers and contradors are still responsible for the defections occurred and it will be repaired during the defect liability period. Consequently, the purposes of this research are to identify the types of defect and percentages of defect during the defect liability period that fell under responsibility and which categories are not Apart from that, this research also implemented in order to spot the consumers (residential owners) right and responsibility during the defections phase. The only scope of the research is focusing on the types of defect that occurred on the new buildings along with that the buildings are still under the defect liability period. The methodology of the research was done by conducting site visits and simple inspection through the survey techniques. Afterward, the data and information acquired during the survey will be identified and analyzed to classify the defects under its respective categories. Apart from that, interview sessions were conducted with some interrelated individual whose involved under the process of construdions and the owners of the residential buildings for the reason of recognizing the respective rights and responsibilities for the defections throughout the defect liability period. As a conclusion, most defect happened during the defect liability period are fully liable by the developers and contractors as long as the rationale of the defections appeared from the developers and contractors themselves, for instant, the poor workmanship and less of material quality. However, should the defects are caused by the negligence of the residents; it would not be accounted as the developer’s liabilities, neither the contractor’s.